Transient Analysis of Fresnel Zone Plates for Ultrasound Focusing Applications - Perez-Lopez S. Sergio; Tarrazo-Serrano D. Danie; Dolmatov D. O. Dmitry Olegovich; Rubio C. Constanza; Candelas P. Pilar (2020, 2020)
Title screen